2001
DOI: 10.1099/00207713-51-1-195
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the filamentous bacterium 'Nostocoida limicola' III from activated sludge.

Abstract: Five strains of the filamentous bacterium ' Nostocoida limicola ' III were successfully isolated into pure culture from samples of activated sludge biomass from five plants in Australia. 16S rRNA gene sequence analyses showed that all isolates were members of the Planctomycetales, most closely related to Isosphaera pallida, but they differed phenotypically from this species in that they did not glide and were not thermotolerant. The ultrastructure of these ' N. limicola ' III isolates was also consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…have been found in foaming activated sludge, let alone Nostocoida Limicola III [17]. Recently, Liu et al [18] and Seviour et al [19] isolated and identified several strains obtained from different wastewater treatment plants in Australia, the Czech Republic, and Italy. They found that the phylogeny of the Nostocoida genus to be very diverse.…”
Section: Foaming Activated Sludge Identification By Non-cultured Basementioning
confidence: 97%
See 1 more Smart Citation
“…have been found in foaming activated sludge, let alone Nostocoida Limicola III [17]. Recently, Liu et al [18] and Seviour et al [19] isolated and identified several strains obtained from different wastewater treatment plants in Australia, the Czech Republic, and Italy. They found that the phylogeny of the Nostocoida genus to be very diverse.…”
Section: Foaming Activated Sludge Identification By Non-cultured Basementioning
confidence: 97%
“…The N. limicola I, N. limicola II, and N. limicola III are low G + C content Gram-positive bacteria, high G + C content Gram-positive bacteria, and Planctomycetes, respectively. Liu et al [18] found that the isolates of N. limicola III was Gram-variable with high G + C content bacteria. The N. limicola sp.…”
Section: Foaming Activated Sludge Identification By Non-cultured Basementioning
confidence: 99%
“…1c) (Giovannoni et al, 1987a, b;Lindsay et al, 2001;Liu et al, 2001;Wang et al, 2002;Fuerst, 2005;Ward et al, 2006). Two electron-dense layers separated by an electron-transparent layer were clearly visible in the ultrastructure of the cell wall.…”
mentioning
confidence: 99%
“…Data from laboratory-scale studies repeatedly show that this organism possesses the phenotype expected of a PAO (Pereira et al, 1996;Mino et al, 1998;Hesselmann et al, 2000;Liu et al, 2001). A metabolic model was reconstructed for the dominant Accumulibacter strain (Clade IIA str.…”
Section: Introductionmentioning
confidence: 99%